Probiotics for constipation in Parkinson’s: A systematic review and meta-analysis of randomized controlled trials - Yin, Shao; Zhu, Fengya (Frontiers in Cellular and Infection Microbiology, 2022)
Background: PD-related constipation may affects both disease occurrence and disease progression. Probiotics, as a potential therapeutic intervention, have attracted the attention of researchers, but the evidence of their efficacy and safety has not been systematically reviewed.AIM: A systematic review and meta-analysis of randomized controlled trials of probiotics in the treatment of PD constipation was conducted to determine the efficacy and safety of probiotics in the treatment of PD constipation.Methods: The Cochrane Central Register of Controlled Trials, Embase, PubMed, and Web of Science were searched from their establishment to June 1, 2022. We included randomized controlled trials of probiotics for the treatment of constipation in patients with PD, with probiotics in the experimental group and a placebo, another treatment, or no treatment in the control group. The primary outcome was the number of bowel movements per week. Secondary outcomes included NMS, GTT, abdominal pain, abdominal distention, constipation, and quality of life scores. Stata15.1 was used to generate a summary of the data and perform a descriptive analysis if necessary. The GRADE tool was used to assess the quality of the evidence and the Cochrane guidelines to assess the risk of bias for each study.Results: Finally, four qualified RCTs were included, comprising 287 participants. Compared with the control group, probiotics could effectively increase the frequency of defecation per week in PD patients (WMD = 1.02. 95%CI: 0.56–1.48, and P < 0.00001), but the heterogeneity was high, and the quality of the evidence was low. There was no significant difference in average stool consistency between patients with PD treated with probiotics and those given a placebo in (WMD = –0.08. 95%CI: –1.42–1.26, and P = 0.908). In addition, the results suggested that probiotics have no obvious effect on additional indicators of gastrointestinal dysfunction, such as GTT, abdominal pain, and abdominal distension, and there is insufficient evidence on their ability to improve NMS and PDQ39-SI. Safety issues should be carefully explained.Conclusion: There is insufficient evidence supporting the use of probiotics to treat constipation in patients with PD. Taking all the results together, we still support the potential benefits of probiotics to treat PD-related constipation.